In search of a nation histories of authority & dissidence in Tanzania - Maddox, Gregory H. (Dar es Salaam Kapsel Educational Publications, 2005)
The double-sided nature of African nationalism - its capacity to inspire expressions of unity, and its tendency to narrow political debate - are explored by sixteen historians. The narrative of the nation of Tanzania, which was created by the anti-colonial nationalist movement, expanded by the Union after the Zanzibar Revolution, and fused by the ideology of Ujamaa by Julius Nyerere, has shaped Tanzanian political discourse for decades, but has not obliterated the great wealth of political discourses and identities which exist within the nation.
Includes bibliographical references and index
Keywords: Nationalism-Tanzania. Politics and culture-Tanzania. Dissenters-Tanzania. Tanzania-Politics and government